Successful live birth after in vitro maturation treatment in a patient with autoimmune premature ovarian failure: a case report and review of the literature. (2nd December 2021) - Chansel-Debordeaux, Lucie; Rault, Elisabeth; Depuydt, Chloé; Soula, Volcy; Hocké, Claude; Jimenez, Clément; Creux, Hélène; Papaxanthos-Roche, Aline
Abstract: Objective: We report a successful live birth after oocytes in vitro maturation (IVM) and fresh embryo transfer in a patient with autoimmune premature ovarian failure (POF) and performed a review of the literature of livebirths obtained after oocytes IVM treatment in this indication. Methods: The patient was a 24-year-old woman with autoimmune POF diagnosed post-partum, who developed autoimmune polyglandular syndrome with serum anti-ovarian and anti-21-hydroxylase antibodies. The patient had typical symptoms of POF: secondary amenorrhea with hypoestrogenism, elevated gonadotropins and infertility; however, the serum anti-Müllerian hormone level and total antral follicle count remained normal. IVM of immature oocytes was performed after the administration of 150 IU highly purified human menopausal gonadotropin for three consecutive days and an injection of 10, 000 IU human chorionic gonadotropin to trigger ovulation. Results: The six oocyte–cumulus complexes collected matured in vitro . After intracytoplasmic sperm injection (ICSI), five embryos were obtained. Pregnancy was achieved after the fresh transfer of two embryos and appropriate endometrial preparation. A normal female child was delivered following a 37-weeks pregnancy characterized by the onset of adrenal insufficiency and unstable diabetes. Conclusions: We report a successful livebirth after IVM treatment in a patient with autoimmune premature ovarian failure (POF). Management of reproductive age women with autoimmune pathology requires fertility counseling. Early diagnosis of autoimmune POF is important for early conception and oocyte preservation, because the only other option at present is ovum donation.